Social life: explanation experience - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2022)
The article reveals the essence of social life as the actions of people who are focused on the values and norms that form the basis of the social order. The history of explaining the causes and mechanisms of these actions in the history of social thought is considered. It is shown that the conscious adherence to the values and norms of the social order is primarily due to the fact that people understand their usefulness for the realisation of their interests. This ensures predictability of behaviour, its social expediency and reciprocity in relations between people. Regulators of socially oriented behaviour are considered to be adherence to the norms of law and morality, recognition of the legitimate nature of power, social expectations, interaction and habitualisation.